2021
DOI: 10.1177/87552930211000358
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of a rehabilitated building in soft soil in Mexico and structural response to the September 2017 earthquakes: Part 1: structural health monitoring system

Abstract: The seismic response of an instrumented 22-story rehabilitated building is presented. The building analyzed is as part of a complex (called CCUT) with three low-rise structures and a common basement founded on soft soil that was built in 1964. Since it was under construction until date, the building tower has experienced differential settlements and tilting. To mitigate such problems, the building has been subjected to several rehabilitations over the years. During the 1985 and 2017 high-intensity earthquakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The results of data processing 2 at the research point with can be seen in table 4 is also the result of the dominant frequency value (f 0 ) that has been obtained and processed using the H / V curve The results of the dominant frequency obtained based on measurements 1 and 2 on the research track based on the classification according to Kanai (1983) and Wahyudin (2019) explain that the dominant frequency value on the research track is a low value and indicates that the earthquake vulnerability in the area around the research is still safe. And the frequency value obtained at the research point is not a single value caused by ground vibrations influenced by quasi resonance from the management building around the dam and the dominant frequency around the location (Vila, 2021).…”
Section: A Dominant Frequency Analysis (F O ) Of Jatibarang Dammentioning
confidence: 86%
“…The results of data processing 2 at the research point with can be seen in table 4 is also the result of the dominant frequency value (f 0 ) that has been obtained and processed using the H / V curve The results of the dominant frequency obtained based on measurements 1 and 2 on the research track based on the classification according to Kanai (1983) and Wahyudin (2019) explain that the dominant frequency value on the research track is a low value and indicates that the earthquake vulnerability in the area around the research is still safe. And the frequency value obtained at the research point is not a single value caused by ground vibrations influenced by quasi resonance from the management building around the dam and the dominant frequency around the location (Vila, 2021).…”
Section: A Dominant Frequency Analysis (F O ) Of Jatibarang Dammentioning
confidence: 86%
“…In this procedure, a simplified mathematical model is used, and the values of the structural parameters necessary to produce an optimal correlation between the measured and calculated responses are estimated. For the latter, the theory of structural analysis and dynamics is used to model the structure and obtain its properties [21,26,30]. Within this category are methods such as the prediction error method (PEM) and stochastic subspace identification (SSI) technique for linear systems.…”
Section: Parametric Analysis Proceduresmentioning
confidence: 99%
“…Currently, state-of-the-art modal analyses of already built structures indicate that there is more than one method with which the dynamic properties of buildings can be identified. These methods can be grouped into two main categories: parametric identification, which establishes a simplified mathematical model with which the measured and calculated responses can be compared, and nonparametric identification, which identifies the system by means of transformations, functions, and mathematical processes [20,21]. Some interesting works determining the dynamic response of heritage and modern structures with irregularities using system identification techniques can be consulted in the references [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Ponzo achieved eigenfrequencies and the equivalent viscous damping factor using an accelerometer [17] and demonstrated that force-balanced accelerometers detected the fundamental frequency of the investigated bridge, which was less than 1 Hz [18]. However, accelerometers are likely to be affected by environmental factors, such as temperature and humidity, and are sensitive to the installation location and orientation [19,20].…”
Section: Introductionmentioning
confidence: 98%